Highly Active Oxygen Evolution Integrating with Highly Selective CO2-to-CO Reduction - Wang, Chaowei; Geng, Laihong; Bi, Yingpu (Nano-Micro Letters, 2025)
Artificial carbon fixation is a promising pathway for achieving the carbon cycle and environment remediation. However, the sluggish kinetics of oxygen evolution reaction (OER) and poor selectivity of CO2 reduction seriously limited the overall conversion efficiencies of solar energy to chemical fuels. Herein, we demonstrated a facile and feasible strategy to rationally regulate the coordination environment and electronic structure of surface-active sites on both photoanode and cathode. More specifically, the defect engineering has been employed to reduce the coordination number of ultrathin FeNi catalysts decorated on BiVO4 photoanodes, resulting in one of the highest OER activities of 6.51 mA cm−2 (1.23 VRHE, AM 1.5G). Additionally, single-atom cobalt (II) phthalocyanine anchoring on the N-rich carbon substrates to increase Co–N coordination number remarkably promotes CO2 adsorption and activation for high selective CO production. Their integration achieved a record activity of 109.4 μmol cm−2 h−1 for CO production with a faradaic efficiency of > 90%, and an outstanding solar conversion efficiency of 5.41% has been achieved by further integrating a photovoltaic utilizing the sunlight (> 500 nm). Highlights: 1 Rational regulation of the coordination environment of surface-active sites on both photoanode and cathode has been demonstrated. 2 Reducing the coordination of FeNi catalysts decorated on BiVO4 photoanodes achieves excellent water oxidation activities of 6.51 mA cm−2 (1.23 VRHE, AM 1.5G). 3 Single-atom cobalt anchoring on N-rich carbon with increased Co–N coordination remarkably promotes CO2 reduction to CO.